Legal Protection for Murder Victims as Perpetrators of Forced Defense From The Perspective of Victimology - Pakpahan, Kartina (Faculty of Law, Universitas Pekalongan, 2024)
Article 1 paragraph (3) and Article 27 paragraph (1) of the 1945 Constitution stipulate that all citizens have equal standing before the law. Furthermore, Article 28 D paragraph (1) states that everyone has the right to recognition, guarantee, protection, and certainty of fair law and equal treatment before the law. These provisions stipulate that all orders in national, social and state life are based on applicable laws and regulations. Therefore, all actions should be carried out according to the law, both by society and law enforcement. Psychologically, everyone does not want to lose their lives and property. In criminal acts, some victims react with resistance and some do not. But among the many crimes, it turns out that there are victims who react with resistance to the point of paralyzing the perpetrator of the crime, even to the point of causing the perpetrator to lose his life. As a result, the victim's self-defense efforts give rise to a case, namely being named a suspect for the crime. Therefore, this study aims to determine how legal protection is for victims of robbery as perpetrators of forced defense from a victimology perspective. This research was conducted using an empirical legal method, using progressive legal theory and legal justice theory. So that through this research, it was found that there was a change in understanding of investigators and investigators at the Indonesian Police that based on legal theory, there is an exception to the determination of a suspect or it can be said as a reason for the elimination of a criminal offense, namely justification and forgiveness as a duty and as self-defense for a crime.